Evidence for Psoriatic Arthritis Impact of Disease (PsAID12) as Core Instrument to Measure Health-Related Quality of Life in Psoriatic Arthritis: A Systematic Review of Psychometric Properties. Issue 1 (January 2020) - Holland, Richard; Højgaard, Pil; Tillett, William; Gossec, Laure; de Wit, Maarten; Christensen, Robin; McHugh, Neil; Gladman, Dafna D.; Mease, Philip; FitzGerald, Oliver; Shea, Beverly; Tugwell, Peter; et al.
Objective: To evaluate and update the evidence for the measurement properties of the Psoriatic Arthritis Impact of Disease (PsAID12) questionnaire to measure health-related quality of life (HRQoL) in psoriatic arthritis (PsA). Methods: The PsAID12 psychometric evidence was gathered in a systematic literature review in PsA (registration number: CRD42016032546). The study quality was appraised using the Consensus-based Standards for the selection of health Measurement Instruments–Outcome Measures in Rheumatology (COSMIN-OMERACT) good methods check-list. Content validity, test–retest reliability, construct validity, longitudinal construct validity, discrimination, and thresholds of meaning were appraised. Additional analyses for construct validity, responsiveness, and sensitivity to change were conducted in available observational data sets after prespecified hypotheses were formulated. Results: Eight publications (129-474 patients) were analyzed. The PsAID12 fulfilled OMERACT criteria for content validity (patients and physicians endorsed content match with PsA HRQoL domain), feasibility (endorsed by patients and physicians), and test–retest reliability (intraclass correlation coefficient: 0.91-0.95). A priori construct validity hypotheses were mostly met: Psoriatic Arthritis Impact of Disease had high correlation with generic ( r = 0.76-0.87) and PsA-specific HRQol measures (0.8), and with measures of physical function (0.66-0.72), work productivity (0.69-0.75), pain (0.83), and fatigue (0.84). Psoriatic Arthritis Impact of Disease had moderate-high correlation with measures of patient global (0.49-0.84) and dermatologic HRQoL (0.36-0.53). Correlations were higher with generic HRQoL measured by short form-36 physical component score (0.47-0.73) versus short form-36 mental component score (0.22-0.60). Three studies confirmed known group validity of PsAID12 according to PsA disease activity. Psoriatic Arthritis Impact of Disease discriminated between change groups in 2 longitudinal studies (standardized response mean: 0.74-0.91, 53 and 105 patients). The minimal clinically important improvement was 3 and 1.4 points. Conclusion: Psoriatic Arthritis Impact of Disease had evidence for good content and construct validity, reliability, and longitudinal construct validity and is ready to evaluate in clinical trials.